Use of medicinal plants for human health in Udzungwa Mountains Forests: a case study of New Dabaga Ulongambi Forest Reserve, Tanzania - Kitula, Rukia A. (Journal of Ethnobiology and Ethnomedicine, 2007)
The dependence of local people on plant medicine from natural forests has a long tradition in Tanzania and is becoming increasingly popular among rural and urban communities due to among others increase in living costs. The study on utilization of medicinal plants for meeting heath care needs was carried out between March 2001 and March 2002 in New Dabaga Ulongambi Forest Reserve, Tanzania. The study aimed at generating necessary data for the Udzungwa Mountains Forest Management project to draft sound Joint Forest Management plans. Specific objectives of the study among others were to assess knowledge associated with utilization of medicinal plants for health care needs as well as factors associated in using plant medicines in the study area. A questionnaire survey, market survey and literature review were used to collect information. Tools used for data analysis were Statistical Packages for Social Science and content analysis. A total of 45 plant species were documented curing about 22 human diseases. Medicinal plants were readily available throughout the year and plentiful in the forest reserve. Roots and leaves were the plant parts harvested for medicinal purposes. Processing of plant medicines involved boiling, pounding, soaking in water and chewing. Distance to health facility, income level of the household and beliefs contributed to the use of plant medicines. The study concluded that medicinal plants play an important role in providing primary health care to the rural communities. It is recommended that in achieving joint forest management (JFM), villagers adjacent to the forest reserve should be sensitised on the importance of JFM through seminars, workshops, drama, school songs or video show. During the development of a joint draft management plan, villagers as an informal institution must define their priority needs of use of parts of the forest in collaboration with the Udzungwa Mountains Forest Management project.